Party System Institutionalization in Asia : Democracies, Autocracies, and the Shadows of the Past - Hicken, Allen; Kuhonta, Erik Martinez (Cambridge : Cambridge University Press, 2014)
This book provides a comprehensive empirical and theoretical analysis of the development of parties and party systems in Asia. The studies included advance a unique perspective in the literature by focusing on the concept of institutionalization and by analyzing parties in democratic settings as well as in authoritarian settings. The countries covered in the book range from East Asia to Southeast Asia to South Asia.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).